Wheater's basic histopathology : a colour atlas and text. - Stevens, Alan, ....-; Lowe, James Steven, ....-; Young, Barbara, 1955- (Philadelphia : Churchill Livingstone, 2007)
This best selling atlas and text of histopathology provides a practical collection of color photomicrographs of diseased human tissue to supplement standard pathology texts. An ideal companion to the renowned Wheater's Functional Histology, this new edition gives more emphasis to the scientific basis of disease and clinicopathological correlations. PART 1: BASIC PATHOLOGICAL PROCESSES Cellular response to injury Acute inflammation, healing, and repair Chronic inflammation Infections of histological importance Amyloidosis Disorders of growth Neoplasia Atherosclerosis Thrombosis and embolism Infarction PART 2: BASIC SYSTEMS PATHOLOGY Cardiovascular system Respiratory system Alimentary system Hepatobiliary system and pancreas Urinary system Lymphoid and hemopoietic systems Female reproductive system Breast Male reproductive system Endocrine system Skin Skeletal system Neuromuscular system Notes on staining techniques